2016
DOI: 10.1021/acs.accounts.6b00051
|View full text |Cite
|
Sign up to set email alerts
|

“Sticky”-Ends-Guided Creation of Functional Hollow Nanopores for Guest Encapsulation and Water Transport

Abstract: Commercial uses of water-transporting aquaporins for seawater desalination and wastewater reclamation/reuse are being investigated in both academia and the industry. Presently, structural complexity, stability, scalability, and activity reconstitution of these costly channel proteins still present substantial challenges to scientists and engineers. An attractive strategy is to develop robust synthetic water channels able to mimic the water-transporting function of aquaporins for utility in the making of next g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 50 publications
0
75
0
Order By: Relevance
“…m-Phenylene-bridged dimer 14 was obtained in 25 % yield through regioselective Suzuki-Miyaura cross-coupling at the 2-positions of dibromides 12 with m-phenylene spacer unit 13 and subsequentd ebrominations at the 5,5'-positions by using Zn/NH 4 Cl. Regioselective Suzuki-Miyaura cross-coupling only at the 9,9'-positions of 4,4',9,9'-tetrakis(pivaloyloxy- Scheme1.Synthesis of p-spacer-bridged dimers 1-3.Reagents and conditions:i )NBS (1.5 equiv), CH 3 CN, 25 8C, 1.5 h, 79 %; ii)a)danB-Bpin(2.0 equiv), Pd 2 (dba) 3 (2 mol %), KOAc (6.0 equiv),1 ,4-dioxane, 100 8C, 2d;b )conc. HCl/ THF = 1:4, 25 8C, 2d,6 6% over two steps;iii) 8,Pd(PPh 3 ) 4 (3 mol %), 2 m K 2 CO 3 aq./1,4-dioxane = 1:3, 100 8C, 1d,2 5%;i v) 9,K 3 PO 4 (2.4 equiv), Pd(OAc) 2 (4 mol%), S-Phos (11mol %), toluene,1 10 8C, 2d,5 6%;v )10,K 3 PO 4 (2.4 equiv), Pd(OAc) 2 (4 mol %), S-Phos (7 mol %), toluene, 110 8C, 1d,7 6%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…m-Phenylene-bridged dimer 14 was obtained in 25 % yield through regioselective Suzuki-Miyaura cross-coupling at the 2-positions of dibromides 12 with m-phenylene spacer unit 13 and subsequentd ebrominations at the 5,5'-positions by using Zn/NH 4 Cl. Regioselective Suzuki-Miyaura cross-coupling only at the 9,9'-positions of 4,4',9,9'-tetrakis(pivaloyloxy- Scheme1.Synthesis of p-spacer-bridged dimers 1-3.Reagents and conditions:i )NBS (1.5 equiv), CH 3 CN, 25 8C, 1.5 h, 79 %; ii)a)danB-Bpin(2.0 equiv), Pd 2 (dba) 3 (2 mol %), KOAc (6.0 equiv),1 ,4-dioxane, 100 8C, 2d;b )conc. HCl/ THF = 1:4, 25 8C, 2d,6 6% over two steps;iii) 8,Pd(PPh 3 ) 4 (3 mol %), 2 m K 2 CO 3 aq./1,4-dioxane = 1:3, 100 8C, 1d,2 5%;i v) 9,K 3 PO 4 (2.4 equiv), Pd(OAc) 2 (4 mol%), S-Phos (11mol %), toluene,1 10 8C, 2d,5 6%;v )10,K 3 PO 4 (2.4 equiv), Pd(OAc) 2 (4 mol %), S-Phos (7 mol %), toluene, 110 8C, 1d,7 6%.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly,t he 1 HNMR study of dimer 1 in variouss olvents revealed that dimer 1 retainedi ts helical conformation regardless of solvent polarity (Figure 7), although it is known that the conformationo ft ypical foldamersu tilizing hydrogen bonds [3][4][5] and the solvophobic effect [2,9] is sensitive to the solvent polarity.A sm entioned above, the biphenylylene-bridged dimer 1 preferentially adopted ah elical form in CDCl 3 while having ar elatively flexible spacer (Figure 6b and Figure 7b). In either 3:2( v/v) CDCl 3 /n-hexane or 3:1( v/v) CDCl 3 /CD 3 OD, the H B and H C proton signals of the quinoliner ing shifted to more upfield positions (Figure 7a and cv s. b).…”
Section: Hn Mr Studies Of Dimersmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In all these cases, the “wheels” employed are based on macrocyclic molecules that are nonplanar and fairly flexible conformationally. In recent years, shape-persistent macrocycles, with noncollapsible and geometrically well-defined skeletons, such as phenylacetylene macrocycles, 9 have attracted considerable attention due to their intriguing functions, including supramolecular gelation, 10 channelized transportation, 11 organic catalysis, 12 molecular recognition 13 and multifunctional self-assembly. 14 Many shape-persistent macrocycles have well-defined surface topography and nanosized cavities with preorganized binding sites, and thus may exhibit enhanced complexation.…”
Section: Introductionmentioning
confidence: 99%